Phenology and yield of raspberry cultivars in subtropical regions in Brazil - Moura, Pedro Henrique Abreu; Campagnolo, Marcelo Angelo; Pio, Rafael; Curi, Paula Nogueira; Assis, Cynthia Natally de; Silva, Thaís Cristina (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the phenology and yield of raspberry cultivars under subtropical conditions in Brazil. The experiment was carried out in the municipalities of Lavras, in the south of the state of Minas Gerais, and of Marechal Cândido Rondon, in the west of the state of Paraná. Seven raspberry cultivars were evaluated, from the species Rubus idaeus (red raspberries, 'Heritage', 'Polana', 'Autumn Bliss', and 'Batum'; and yellow raspberries, 'Golden Bliss' in Lavras, and 'Fall Gold' in Marechal Cândido Rondon) and R. niveus (black raspberry), besides a hybrid (Boysenberry) between R. idaeus and blackberry (R. ursinus). Phenological traits (flowering and harvest time) and production ones were evaluated during two production cycles, and the physicochemical characteristics of the fruits (dimensions, titratable acidity, and soluble solids content) were determined. Rubus idaeus cultivars and the interspecific hybrid did not adapt to the climatic conditions of west of Paraná state, with low fruit production. However, the black raspberry is an excellent crop option for this region, with high yield (above 25 Mg ha-1) and fruit quality (ratio of 9.3). In south of Minas Gerais, the raspberries show good adaptation, especially the black raspberry (18.2 Mg ha-1), the yellow raspberry (5 Mg ha-1), and the red raspberry 'Batum' (4.4 Mg ha-1).